2021
DOI: 10.1002/smll.202102558
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Enhanced Efficiency and Operational Stability of Nonfullerene Organic Solar Cells via Solid‐Additive‐Mediated Aggregation Control

Abstract: The additive strategy is widely used in optimizing the morphology of organic solar cells (OSCs). The majority of additives are liquid with high boiling points, which will be trapped within device and consequently deteriorate performance during operation. In this work, solid but volatile additives 2‐(4‐fluorobenzylidene)‐1H‐indene‐1,3(2H)‐dione (INB‐F) and 2‐(4‐chlorobenzylidene)‐1H‐indene‐1,3(2H)‐dione (INB‐Cl) are designed to replace the common 1,8‐diiodooctane (DIO) in nonfullerene OSCs. These additives pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 73 publications
(81 reference statements)
1
47
0
Order By: Relevance
“… 24 26 The second type of SADs can effectively decrease the adsorption energy of acceptors to improve π–π stacking through the attractive interaction between the SADs and acceptors, thereby resulting in an enhancement of light absorption and electron mobility. 27 , 28 The last type of SADs with high crystallinity can form well-developed nanoscale phase separation by restricting the over self-aggregation of acceptors in the process of film formation and then facilitating the donors to access the remaining space of SADs during the TA process. 29 , 30 Although these new strategies of SADs have shown many attractive features, the fundamental understanding of the relationship of SAD structures, active layer morphology, and OSC performance is missing.…”
Section: Introductionmentioning
confidence: 99%
“… 24 26 The second type of SADs can effectively decrease the adsorption energy of acceptors to improve π–π stacking through the attractive interaction between the SADs and acceptors, thereby resulting in an enhancement of light absorption and electron mobility. 27 , 28 The last type of SADs with high crystallinity can form well-developed nanoscale phase separation by restricting the over self-aggregation of acceptors in the process of film formation and then facilitating the donors to access the remaining space of SADs during the TA process. 29 , 30 Although these new strategies of SADs have shown many attractive features, the fundamental understanding of the relationship of SAD structures, active layer morphology, and OSC performance is missing.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the dual solvent affected the crystalline order of D18-Cl. [38][39][40] The absorption spectrum of the D18-Cl/Y6 bilayers is detailed in Figure 2b, with the peak around 550 nm attributed to D18-Cl and the peak around 800 nm being the contribution of Y6. The films of D18-Cl(CB þ CF)/Y6 and D18-Cl(CB þ THF)/Y6 displayed increased absorption throughout the spectral range, mainly in 400-600 nm, further suggesting that the dual solvent improved the crystallization of D18-Cl, making it more ordered, while protecting D18-Cl from being washed out and improving photon utilization.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent additives accelerate the burn-in degradation process of the active layers, while the solid additives significantly suppress the process due to their volatility. The results indicated that the solid additive is a promising material in OSC manufacturing as it improves the photostability and PCE 76 It appeared that the D-A-type structure is not essential for small organic additives to have positive effects in OSCs. For instance, a dihalogenated indanone end group IC-FI (Fig.…”
Section: Nanomaterialsmentioning
confidence: 99%